Mind, meaning, and knowledge themes from the philosophy of Crispin Wright - Coliva, Annalisa, 1973- (Oxford : Oxford University Press, 2013)
A collective exploration of major themes in the work of Crispin Wright, one of today's leading philosophers. The distinguished contributors address a variety of issues, including truth realism, anti-realism, relativism, and scepticism, and testify to Wright's seminal work on language, mind, metaphysics, and epistemology.
Includes index.
Description based on online resource; title from PDF title page (viewed on Oct. 30, 2012).
Keywords: Wright, Crispin, -- 1942-